Influence of Combination Modes on Gas-Assisted Transverse Injection - Chenglong YAN; Gangqiang WU; Chuanjin JIANG; Geng LI; Kangkang GUO; Ruirui BAO; Wei LIN (气体物理)
An in-depth study of fuel injection atomization in the expanded configuration under supersonic inflow conditions is extremely important for developing air-breathing rotating detonation engines. Combinations of H2-assisted transverse jets designed to enhance penetration depth of liquid and gas jets were investigated via Euler-Lagrange simulation method. The flow field structure and the enhancement mechanism of liquid jet atomization under the gas-liquid and liquid-gas combination modes were intensely studied. The hydrogen distribution and the atomization characteristics of the transverse liquid jet under other combinations were also summarized. Results show that H2 and liquid spray distribution produces inconsistent characteristics under different combination methods. Related aggregation phenomena of liquid spray can be corrected by changing the combination method. When the static temperature of incoming flow is high enough, the gas-liquid combination mode is recommended; otherwise, the liquid-gas combination mode based on active fuel such as H2 is recommended. The gas-liquid distance has little effect on the breakup of droplets. However, the larger the gas-liquid distance, the lower the penetration depth of the liquid jet. The same time, a prominent empty flow area appears on the lower wall surface. Results also show that the recommended gas-liquid spacing is 5 mm in the gas-liquid combination mode. The breakup of droplets under the gas-liquid combination is mainly caused by the shearing effect of the downwash flow field, and the liquid-gas combination is mainly due to the shearing effect of the upwash flow field.